Drugs Currently Undergoing Preclinical or Clinical Trials for the Treatment of Overactive Bladder: A Review - Silvia Joseph, MBBS; Steffi A. Maria, MD; Jacob Peedicayil, MD (Current Therapeutic Research, 2022)
ABSTRACT: Background: Overactive bladder (OAB) is a common clinical condition for which current drug treatment comprises drugs blocking the cholinergic nerve supply, or augmenting the adrenergic nerve supply, to the detrusor muscle of the urinary bladder. Current treatments have drawbacks, including lack of efficacy and the development of adverse effects in some patients. Hence, new and better drugs for treating OAB will be clinically useful. Objective: This review is meant to provide information on drugs currently undergoing preclinical or clinical trials for the treatment of OAB published in journal articles or elsewhere. Methods: The cited articles were retrieved from PubMed and Google Scholar from January 1, 1990, to December 31, 2021. The search terms used were contraction or contractility, detrusor, inhibition, isolated or in vitro, in vivo, overactive bladder, and relaxant effect or relaxation. Results: There are 4 classes of new drugs under various stages of development for the treatment of OAB. These are drugs acting on the autonomic nerve supply to the detrusor muscle of the urinary bladder that include the anticholinergics tarafenacin and afacifenacin and the β3 adrenoceptor agonists solabegron and ritobegron; drugs acting on ion channels in the detrusor muscle (eg, potassium channel openers and calcium channel blockers), drugs acting on cellular enzymes like phosphodiesterase-5 inhibitors and Rho kinase inhibitors, and drugs acting on miscellaneous targets (eg, pregabalin and trimetazidine). Conclusions: Drugs currently used to treat OAB target only the cholinergic and adrenergic cellular signalling pathways. There are many other drugs under trial targeting other cellular pathways that may be useful for treating OAB. Their approval for clinical use might improve the treatment of patients with OAB. (Curr Ther Res Clin Exp. 2022; 83:XXX–XXX)